ANALISIS PENDAPATAN USAHATANI CENGKEH DI DESA TALAGA KECAMATAN DAMPELAS KABUPATEN DONGGALA - Asrawati, Asrawati; Antara, Made (AGROTEKBIS, 2017)
This research aimed to determine the income of clove farming in Talaga Village; Dampelas Sub District of Donggala Regency. The research was carried out from October to November 2016. Sixty respondents were selected from a total population of 150 clove farmers. The analysis method used was the analysis of income. The results of the analysis showed that the clove production was 228 kg/ha/year at a price of IDR 90,000/kg, the average total cost was IDR 6,100,118/ha/year or IDR 5,258,772/ha/year, the average revenue generated was IDR 35,145,000/ha/year or IDR 30,297,413/ha/year with the average income of the clove farmers was IDR 29,047,881/ha or IDR 25,041,276/ha/year. These values indicate that the total revenue is greater than the cost incurred by the clove farmers in The Village of Talaga.Â Key Words: Cost, clove farming, income and revenue.